Synthesis and Characterization of Chitosan- Alginate for Controlled Release of Isoniazid Drug - Sari Edi Cahyaningrum; Nuniek Herdyastuti; Nur Qomariah (Indonesian Journal of Chemistry, 2015)
The aim of this research was to synthesize and characterize chitosan-calcium alginate as matrix isoniazid encapsulation to produce controlled release isoniazid drug. The microparticles were evaluated for surface morphology, functional groups, size particles, drug content and swelling index. The drug release kinetic was investigated at gastric and intestinal artificial pH. The results showed that isoniazid-calcium alginate-chitosan has majority particle diameter of 1001-1500 nm. The release mechanism of isoniazid was through combination of erosion and diffusion.